Definitive chemoradiotherapy for patients with malignant stricture due to T3 or T4 squamous cell carcinoma of the oesophagus - Kaneko, K (Nature Publishing Group, 2003)
We retrospectively investigated the efficacy and feasibility of concurrent chemoradiotherapy for patients with severe dysphagia caused by oesophageal squamous cell carcinoma. Concurrent chemoradiotherapy was performed in 57 patients with T3 or T4 disease containing M1 lymph node (LYM) disease. Chemotherapy consisted of protracted infusion of 5-fluorouracil (5-FU) 400 mg m(−2) 24 h(−1) on days 1–5 and 8–12, combined with 2-h infusion of cisplatin (CDDP) 40 mg m(−2) on days 1 and 8. Radiation treatment at a dose of 30 Gy in 15 fractions of the mediastinum was administered concomitantly with chemotherapy. A course schedule with 3-week treatment and a 1 to 2-week break was applied twice, with a total radiation dose of 60 Gy, followed by two or more courses of 5-FU and CDDP. In all, 24 patients (42%) achieved a complete response, and the 3-year survival rate was 19%. Major toxicities were leukocytopenia and oesophagitis, and there were two (4%) treatment-related deaths. In contrast, 22 patients with T3 disease survived longer than 35 patients with T4 disease (P=0.001); however, the survival rate in 15 patients with M1 LYM disease did not differ significantly from that in 42 patients without M1 LYM disease (P=0.3545). Our results indicate that definitive chemoradiotherapy is potentially curative for locally advanced oesophageal carcinoma with malignant stricture. The efficacy and survival of patients treated with this regimen are related to the T factor.